Design and construction of a Reduced Scale Model to Measure Lightning Induced Voltages over an Inclined Terrain (2015)
In this paper is presented the design and construction of a reduce scale model indented to be used for measuring Lightning induced voltages on overhead lines placed over an inclined terrain. Here we present technical details of the source developed for achieve a fast impulse that represent a lightning. The experiment, although, is a first approximation to the phenomenal, is useful for validate numerical methods which are more flexible for future.  Additionally, several simulations are done by means of the FDTD method with the aim to show the expected measurements of the reduced scale model.